MICROELEMENT PREPATIONS AND THEIR IMPORTANCE IN THE BODY ANTIGYPOTHYROID AGENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article will talk about microelement preparations and their biological significance in the body, as well as the mechanism of action and application of antihyprotireoid agents. Trace elements are an important component of enzymatic processes, the immune system and metabolism. Their deficiency can be the cause of various diseases, for this reason, microelement preparations are used. Iodine, iron, zinc, and selenium in particular are essential for the body, and their pharmacological significance has been extensively studied. The article also details thyroid failure (hypothyroidism), its resulting adverse effects, and antigypotireoid agents used to eliminate them, including L-thyroxine, combined hormone drugs, and iodine-containing drugs. These drugs are aimed at normalizing thyroid function and reducing symptoms associated with hypothyroidism. The article will highlight the use of drugs against this and related diseases.